Trinidad and Tobago: assessing the impact of climate change on cocoa and tomato - Eitzinger, Anton; Farrell, Aidan D.; Rhiney, Kevon; Carmona, Stephania; Loosen, Irene van; Taylor, Michael (2015)
This policy brief describes work carried out by CIAT in partnership with the University of the West Indies (UWI), which used climate predictions and crop suitability models to assess the likely impact of climate change on crops grown in Trinidad & Tobago. Key policy recommendations are provided.